Bemiparin in the treatment of a patient with a habitual miscarriage - N K Tetruashvili; A A Agadzhanova; T B Ionanidze (IP Berlin A.V., 2017)
Clinical observation is outlined - conducting pregnancy in a 43-year-old patient with low-risk thrombophilia, a habitual miscarriage, and venous thrombosis of cerebral vessels in an anamnesis. The results were obtained, indicating a favorable clinical outcome when the drug was administered in therapeutic doses, no side effects were recorded. It was possible to achieve the prolongation of pregnancy until the deadline in the absence of thrombotic and hemorrhagic complications. There were no thromboses during pregnancy and in the postpartum period, thrombocytopenia, bleeding in the II and III trimesters of pregnancy. At delivery, blood loss was 700 ml. Anticoagulant therapy with bemiparin was continued for 6 weeks postpartum period for the prevention of thrombotic complications.